Factors Associated with Turnover Intention Among Newly Graduated Nurses - (:unkn) unknown (My University, 2019)
Saudi Arabia faces many challenges to retain experienced and newly graduated nurses (NGNs), similar to Western and Asian countries. The turnover rate of Saudi nurses has reached 50% (Abu Zinadah, 2006) and about 38% out of 172,483 nurses are Saudi (MOH, 2017). Turnover needs to be urgently addressed to secure the future supply of nurses for Saudi Arabia. Despite government efforts to address the workforce shortage, turnover has increased. Research shows that job stress, work environment satisfaction, preceptorship experience, and role conflict and ambiguity are key factors that contribute to turnover intention. It is important for policymakers and nurse leaders to understand the factors (personal and systems) that lead nurses to leave the workforce. The purpose of this study is to examine the association between nursing characteristics, job stress, role conflict and ambiguity, preceptorship experience, work environment satisfaction, and turnover intention among Saudi NGNs. The study featured an exploratory correlational design to survey a convenience sample of n=238 Saudi NGNs during the summer of 2018. Participants have the Saudi nationality, graduated within the past five years, with less than three years of work experience, and work in one of the hospitals in Jeddah or Makkah, Saudi Arabia affiliated with the Ministry of Health. All instruments were translated into Arabic and appropriately tested prior to conducting the study. Results of the study indicated that role conflict and ambiguity are strong predictors of turnover intention. Work environment satisfaction was a common predictor of turnover intention. The findings align with similar studies in other countries. Job stress and positive preceptorship experience were indirectly correlated with turnover intention. Future studies will focus on addressing role conflict and ambiguity, enhancing work environment satisfaction for NGNs, and determine optimal preceptor relationships. Research focused on other parts of Saudi Arabia as well as non-Saudi born nurses will provide further understanding of the factors associated with turnover intention among Saudi NGNs.
Keywords: Job Stress; Newly Graduated Nurses; Preceptorship Experience; Role Conflict and Ambiguity; Turnover Intention; Work Environment Satisfaction